Aplikasi Actinomycetes dan Bakteriofag pada Tomat Sambung untuk Mengendalikan Penyakit Layu Bakteri Ralstonia solanacearum dan Meningkatkan Hasil Buah - Lisa Navitasari; Tri Joko; Rudi Hari Murti; Triwidodo Arwiyanto (Jurnal Ilmu Pertanian Indonesia, 2022)
Ralstonia solanacearum (Smith) is a soil-borne pathogen that causes bacterial wilt disease and is a complex species in races, biovars, phylotypes, and strains of various pathogenicities. As a result, the pathogen is difficult to control. An alternative control is by applying actinomycetes and bacteriophages on tomato grafted with resistant rootstock. This study aims to find the best combination in controlling bacterial wilt disease among grafted tomato plants and/or actinomycetes and/or bacteriophage treatments to increase yields. The graftings were between Amelia (East West, Indonesia) or H7996 (AVRDC) as rootstocks, and Servo (East West, Indonesia) as the susceptible scion. The grafting used the tube method, and the experimental design was a randomized completely block design with the grafted plants treated by actinomycetes and/or bacteriophages with three replications. The results indicated that actinomycetes application on plants grafted with Amelia rootstock or H7996 and the application of bacteriophages on susceptible varieties (Servo) could be the best alternative treatment in controlling the bacterial wilt disease. The susceptible varieties with the actinomycetes or bacteriophages application could even increase fruit yields higher than the grafted tomatoes treated with actinomycetes or bacteriophages. In fact, the susceptible tomato varieties with bacteriophage treatment showed high fruit yield. Keywords: actinomycetes, bacteriophages, bacterial wilt disease, fruit yield, Ralstonia solanacearum